Th9 cells provide protective TB immunity - Xia, Mei; Blazevic, Azra; Ning, Huan; Eickhoff, Christopher S.; Storer, Chad E.; Head, Richard D.; Liu, Jianguo; Jarvela, Jessica; Stoeckel, David; Rakey, Erin; Tennant, Jan; Miller, Daniel L.; et al. (Frontiers in Immunology, 2025)
IntroductionCD4+ Th9 cells have been associated with inflammatory and allergic diseases. IL-9/Th9 can function as both positive and negative immune regulators, but their protective effects against Mycobacterium tuberculosis(Mtb) are unknown. We found that Th9 cells were associated with mycobacteria-specific T cell responses primed by latent tuberculosis infection and BCG vaccination.MethodsTo study TB-specific Th9 protective effects, we generated Th9 cells from ESAT6-specific TCR transgenic mice and healthy human donors.ResultsBoth murine and human Th9 cells significantly inhibited intracellular mycobacterial growth. In both in vitro models, IL-9 neutralization strongly reduced Th9 protective effects, and IL-9 treatment alone inhibited intracellular mycobacteria. ESAT-6-specific Th9 and Th1 cells were adoptively transferred into naïve Rag1/2-/- recipients before aerosol Mtb infection. Th9 cells provided robust immunity as protective as Th1 cells, significantly reducing bacteria and pathologic changes post-infection. Differential persistence of Th9 vs. Th1 cell phenotypes was confirmed in vivo, and lung tissue qRT-PCR studies demonstrated the absence of IFN-γ responses in Th9-transferred mice, combined with unique expression of the Th9 specific markers IL-9, IL-10 and PU.1.DiscussionTh9 cells can provide important protection against Mtb infection, and should be targeted with future TB vaccine strategies. Furthermore, Th9 cells appear to utilize a novel protective mechanism independent from Th1-mediated protective responses.